Distribuição geográfica e modelagem de nicho de espécies endêmicas de Erythroxylaceae na região neotropical - Cordeiro, Luciana Silva (2013)
The high species richness and endemism in the tropical region is influenced by the amount of vegetation types and environmental conditions favorable for the maintenance of diversity. For this study we selected the genus Erythroxylum, which in Brazil is one of the most important centers of endemism, totaling 74 species with restricted distribution in the country. Erythroxylum are recognized in 19 sections, nine of which are represented in the flora. From previous knowledge about the distribution patterns, areas of endemism and species information obtained about the genre, the premise of this study are: (1) species are more taxonomically close phylogenetic niche conservatism (2) areas of endemism are basic units where there is overlap of a complex group of species that co-ocorring restricted to certain locations, (3) environmental filtering and abiotic factors acting as limiters for the survival and dispersal of plant species and help to understand the limits of plant distribution. Our hypothesis is that the distribution of taxonomically close species may be the result of a close relationship between environmental variables and soil. The aim of this study is to investigate which environmental factors could be influencing the current distribution of species of Erythroxylum in Brazilian territory. The sites of occurrence of the species were obtained from information from the virtual collection of CRIA and databases yielded by different groups. To understand the distribution of species and sections in which these are inserted, and confirmation of the centers of richness were generated models using environmental layers available by Wordclim and maximum entropy algorithm. To analyse the preferences of the species as climatic variables and soil in a crop of Brazilian territory were generated models of spatial distribution. The species analysed were the main centers of richness and endemism coincide in places near the transition between areas in Brazil. Some taxonomic sections could be delimited in space, and the distribution associated with different phytogeographic domains. The models show higher affinity of the genre to places with strong seasonality and climate presence of shallow soils and acids.